Mechanisms of Cr and Mo Enrichments in the Passive Oxide Film on 316L Austenitic Stainless Steel - Wang, Zuocheng; Paschalidou, Eirini-Maria; Seyeux, Antoine; Zanna, Sandrine; Maurice, Vincent; Marcus, Philippe (Frontiers in Materials, 2019)
An approach preventing contact to ambient air during transfer from liquid environment for electrochemical treatment to UHV environment for surface analysis by X-Ray Photoelectron Spectroscopy and Time-of-Flight Secondary Ion Mass Spectrometry was applied to study the mechanisms of Cr and Mo enrichments in the passive oxide film formed on 316L austenitic stainless steel. Starting from the air-formed native oxide-covered surface, exposures were conducted in aqueous sulfuric acid solution first at open circuit potential and then under anodic polarization in the passive range. At open circuit potential the thickness of the bi-layered oxide film was observed to decrease and the enrichments of both Cr(III) and Mo, mostly Mo(VI), to markedly increase as well as the film hydroxylation. This is due to preferential dissolution of the Fe(III) oxide/hydroxide, not compensated by oxide growth in the absence of an electric field established by anodic polarization. Anodic polarization in the passive domain causes the bi-layered structure of the oxide film to re-grow by oxidation of iron, chromium and molybdenum, without impacting the Cr enrichment and only slightly mitigating the Mo enrichment. De-hydroxylation of the inner layer is also promoted upon anodic polarization. These results show that the treatment of the surface oxide film in acid solution at open circuit potential enhances Cr and Mo enrichments and promotes hydroxylation. Passivation by anodic polarization allows dehydroxylation, yielding more Cr oxide, without markedly affecting the Mo enrichment, also beneficial for the corrosion resistance.